"CLINICAL AND PATHOGENETIC ASPECTS OF DISEASES OF HARD TISSUES OF TEETH AND PERIODONTAL IN PATIENTS WITH THYROID DYSFUNCTION" - Ro'zimurodova Zilola Shuxratovna (Journals Park Publishing, 2022)
The endocrine system is a system of endocrine glands localized in the central nervous system, various organs and tissues, is one of the main systems of regulation of the body. The endocrine system exerts a regulating influence through hormones.
Keywords: genetically; system; injuries